Methylation of Ir(iii)-tetrazolato complexes: an effective route to modulate the emission outputs and to switch to antimicrobial properties. Issue 36 (11th September 2017) - Fiorini, Valentina; Zanoni, Ilaria; Zacchini, Stefano; Costa, Anna Luisa; Hochkoeppler, Alejandro; Zanotti, Valerio; Ranieri, Anna Maria; Massi, Massimiliano; Stefan, Alessandra; Stagni, Stefano
Abstract : The conversion of neutral to cationic Ir(iii ) tetrazolato complexes enables the red-shift of emission and the switch-on of antibacterial properties against Gram(+) D. radiodurans . Abstract : Two neutral cyclometalated Ir(iii )-tetrazolato complexes that differ by variations of the substituents on either the phenylpyridine or the tetrazolate ligand have been converted into the corresponding methylated and cationic analogues. NMR ( 1 H and 13 C) characterization of the Ir(iii ) complexes provided the results in agreement with the chemo- and regioselective character of methylation at the N-3 position of the Ir(iii )-coordinated tetrazolato ring. This evidence was further corroborated by the analysis of the molecular structures of the cationic complexes obtained by X-ray diffraction. In view of the photophysical properties, the addition of a methyl moiety to neutral Ir(iii ) tetrazolates, which behave as sky-blue or orange phosphors, caused a systematic red shift of their phosphorescence output. The transformation of neutral Ir(iii ) tetrazolates into cationic Ir(iii )-tetrazole complexes was screened for any eventual antimicrobial activity in vitro against Gram negative ( E. coli ) and Gram positive ( D. radiodurans ) microorganisms. While both kinds of complexes were not active against E. coli, the conversion of the neutral Ir(iii ) tetrazolates into the corresponding methylated and cationic Ir(iii )tetrazole derivatives determined the turn-on of a good to excellent antimicrobial activity toward Gram positive Deinococcus radiodurans, a non-pathogenic bacterium that is listed as one of the toughest microorganisms in light of its outstanding resistance to radiation and oxidative stress.